How do Self-Regulation and Retention in Math relate with Classroom Learning Environment: Students’ Perspective Muhammad Anwer1: Sajid Masood, Muhammad Naeem Sarwar (PJDOL, 2023)
This study investigated relationhip of self-regulation (SR) with retention in Math and Classroom Learning Environment (CLE) through quantitative approach based on survey method. 10th grade students from Public Schools of Punjab were the population of the study. Using random sampling, 997 respondents (Boys = 489, Girls = 508) from two districts (conveniently) were selected. The CLE was explored by using WIHIC scale (Fraser, 2007).